STRENGTHENING SCHOOL PRINCIPAL SUPERVISION, LEARNING ORGANIZATION, AND CREATIVITY IN IMPROVING CLASSROOM MANAGEMENT EFFECTIVENESS - Purnomo, Dwi; Wulandari, Dian; Wulandari, Farida (Yayasan Education and Social Center, 2025)
This study aims to analyze the influence of principal supervision, learning organization, and creativity on classroom management effectiveness among civil servant teachers at public elementary schools in Cisauk District. The research method used is quantitative, utilizing SPSS for statistical calculations. The research sample consists of 120 teachers selected through purposive sampling from a population of 221 teachers. Data were collected using questionnaires that had been tested for validity and reliability. The results showed that: (1) Principal supervision had a direct positive effect on classroom management effectiveness; (2) Learning organization had a direct positive effect on classroom management effectiveness; (3) Creativity had a direct positive effect on classroom management effectiveness; (4) Principal supervision has a direct positive effect on creativity; (5) Learning organization has a direct negative effect on creativity; (6) There is an indirect effect of principal supervision on classroom management effectiveness through creativity; (7) There is no indirect effect of learning organization on classroom management effectiveness through creativity. The implications of this study emphasize the importance of improving the quality of principal supervision, strengthening learning organizations that maintain space for creativity, and encouraging teacher innovation in classroom management. It is recommended that schools conduct regular training and seminars to improve these three variables.